Dynamics of welded rails gap and hardness of rail base - Zaitseva, Tatyana I.; Blinova, Irina V; Uzdin, Aleksandr M. (Zielona Góra: Uniwersytet Zielonogórski)
The problem of gap estimation for a break of a continuous welded rail is studied. The track is represented as a semi-infinite rod on elastic-based damping. Static and dynamic solutions are obtained. It is shown that during the rail break, the dynamic factor does not exceed 1.5. We derive equations for thermal deformation of the welded rail of jointless track on an elastic foundation in the presence of the insert into the base with another characteristic stiffness.
Keywords: continuous welded rail; stress-strain state